The factors analysis of influencing purchase intention on Laf Project fashion products with the utilization of Shopee live streaming features - Solihin, Jajang Badru; Rachmawati, Indira (Indonesian Journal of Multidisciplinary Science, 2024)
This study aims to analyze the factors that affect purchase intention of potential buyers towards Laf Project fashion products by utilizing the Shopee Live Streaming feature. This study employs a quantitative method, utilizing a survey approach to collect data from respondents who have used the Live streaming feature at the LAF Project fashion store. The structured data collection process gathers information on respondents' experiences with the Live streaming feature, which were analyzed using statistical methods to address the research questions and draw conclusions based on the findings. The results of the analysis in this study show that several factors significantly affect consumer purchase intention, namely, the attraction and cognitive assimilation variables mediate the relationship between real-time interaction, shopping guidance, visibility, and media richness with consumer purchase intentions, while influencer credibility in the context of this research problem does not have a significant impact on consumers' purchase intention. The research contributes to the fields of digital marketing and e-commerce by identifying the key factors that drive purchase intention through live streaming, which can offer practical insights for fashion brands and online retailers looking to optimize their sales strategies in live commerce environments.